2013
DOI: 10.3920/bm2012.0049
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in Clostridium difficile infection: reviewing the need for a multistrain probiotic

Abstract: In the past two years an enormous amount of molecular, genetic, metabolomic and mechanistic data on the hostbacterium interaction, a healthy gut microbiota and a possible role for probiotics in Clostridium difficile infection (CDI) has been accumulated. Also, new hypervirulent strains of C. difficile have emerged. Yet, clinical trials in CDI have been less promising than in antibiotic associated diarrhoea in general, with more meta-analysis than primary papers on CDI-clinical-trials. The fact that C. difficile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 61 publications
0
37
0
4
Order By: Relevance
“…Hell et al (363) have suggested that a combination of different probiotic strains may be more useful to reduce C. difficile infection. It is noteworthy that fecal microbiota transplantation (FMT) is an emerging treatment to restore the normal microbial homeostasis after antibiotic agents have disrupted the intestinal microbiota, leading to C. difficile-associated diarrhea.…”
Section: Therapeutic Effects Against C Difficile-associated Diarrheamentioning
confidence: 99%
“…Hell et al (363) have suggested that a combination of different probiotic strains may be more useful to reduce C. difficile infection. It is noteworthy that fecal microbiota transplantation (FMT) is an emerging treatment to restore the normal microbial homeostasis after antibiotic agents have disrupted the intestinal microbiota, leading to C. difficile-associated diarrhea.…”
Section: Therapeutic Effects Against C Difficile-associated Diarrheamentioning
confidence: 99%
“…Further, the act of transferring the fecal contents from one person to the next often dissuades some from this procedure. Results of probiotic therapy and monoclonal antibody treatment are either inconclusive or still in clinical trials, respectively (19,20). Therefore, there is a need for new treatments which better target C. difficile without collateral damage to the protective commensal species.…”
mentioning
confidence: 99%
“…23 The multiple stages in the progression from C difficile colonization to infection argue that a multistrain probiotic is likely to be more effective than a single-stain probiotic both in the prevention of disease and in nosocomial transmission. 17 There is emerging evidence regarding differences in the composition of the gut microbiome in established CDD cases compared with non-CDD diarrhea controls and/or healthy individuals. 24,25 However, a greater understanding is needed regarding Box 2 Mechanisms by which exposure to antibiotics results in CDD Depletion of the gut flora resulting in impaired colonization resistance to C difficile Exertion of stress on vegetative C difficile organisms resulting in exotoxin secretion and, thereby, mucosal inflammation the characteristics of the gut microbiota that may be resistant to antibiotic treatment or the development of CDD after antibiotic exposure in advance of disease onset.…”
Section: What Are Probiotics?mentioning
confidence: 99%
“…13 Several properties of probiotic organisms identified in vitro and in vivo may allow them to replenish the antibiotic-depleted gut flora to restore colonization resistance, and also enhance the integrity and barrier function of the gut epithelium, and therefore prevent or ameliorate CDD (Box 3). [14][15][16][17] The particular mechanisms of action that are most important in the prevention of CDD and the degree to which these are shared widely among different probiotic organisms or are species or strain specific are unknown. In vitro studies have demonstrated that a range of microbes inhibit C difficile [18][19][20] and also reduce the inflammation caused by C difficile infection.…”
Section: What Are Probiotics?mentioning
confidence: 99%